Palangka Raya City Community’s intent to pay motor vehicle tax at the Technical Implementation Unit, Palangka Raya Regional Revenue Services - Harjoni, Harjoni (JSM: Jurnal Sains Manajemen, 2024)
This study investigates the impact of attitudes, subjective norms, and perceived control factors on individuals’ intention to pay motor vehicle tax and the influence of intention and control variables on post-payment behaviour of motor vehicle tax at UPT PPD Palangka Raya. The utilized framework is the theory of planned behaviour, specifically the evolution of the Theory of Reasoned Action (Fishbein), employing multiple linear regression analytic techniques. Four hundred individuals who made motor vehicle tax payments at UPT PPD Palangka Raya were selected for sampling. The analysis findings indicate that most motor vehicle taxpayers at UPT PPD Palangka Raya are adult government employees (PNS), predominantly male, with a high school education and an income ranging from above 1 million to 3 million rupiahs. However, there is still a deficiency in public confidence towards UPT PPD Palangka Raya as a whole. The provision of motor vehicle tax payment receipts is influenced by factors such as the credibility of personnel, environmental conditions, and technical services. Additionally, close individuals such as family members, close friends, and neighbours can serve as references and motivators for paying vehicle tax. The people of Palangka Raya city demonstrate a strong willingness and punctuality in paying motor vehicle tax, despite income being an inhibiting factor and the law acting as a compulsion factor. The resale price of motorized vehicles also plays a factor in willingness. It is worth noting that attitude has a significant impact on intention, as well as societal norms. Subjectivity does not have a substantial impact on intention. However, control variables have a substantial impact on intention. Additionally, both intention and control factors significantly influence the post-payment behaviour of motor vehicle tax